Live Cell Imaging Reveals the Dynamics of Telomerase Recruitment to Telomeres - Schmidt, Jens C. (Cell, 2016)
Telomerase maintains genome integrity by adding repetitive DNA sequences to the chromosome ends in actively dividing cells, including 90% of all cancer cells. Recruitment of human telomerase to telomeres occurs during S-phase of the cell cycle, but the molecular mechanism of the process is only partially understood. Here, we use CRISPR genome editing and single-molecule imaging to track telomerase trafficking in nuclei of living human cells. We demonstrate that telomerase uses three-dimensional diffusion to search for telomeres, probing each telomere thousands of times each S-phase but only rarely forming a stable association. Both the transient and stable association events depend on the direct interaction of the telomerase protein TERT with the telomeric protein TPP1. Our results reveal that telomerase recruitment to telomeres is driven by dynamic interactions between the rapidly diffusing telomerase and the chromosome end.